A unique thermostable and organic solvent tolerant lipase from newly isolated Aneurinibacillus thermoaerophilus strain HZ: physical studies - Masomian, Malihe; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (Springer, 2010)
A newly isolated thermophilic bacterium, Aneurinibacillus thermoaerophilus strain HZ, from a hot spring recreational area (Sungai Kelah, Malaysia), showed an extracellular lipase activity. It was identified based on 16S rRNA sequencing, where phylogenetic analysis revealed its homology to Aneurinibacillus thermoaerophilus. The strain produced a lipase that was stable in various organic solvents such as dimethyl sulfoxide, toluene, p-xylene, and hexane. In order to increase lipase production, optimization of physical factors which affected the growth and lipase production was studied. The optimal growth was obtained at 50°C and pH 8.0; while the maximal lipase production was achieved in the logarithmic decline phase at 60°C and pH 7.5 with 7% starting inoculum and 150 rev/min shaking rate for 48 h incubation.